1999
DOI: 10.1678/rheology.27.53
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Viscoelasticity of Ionomers Based on Ethylene-co-Methacrylic Acid Copolymer in the Melt State.

Abstract: Dynamic viscoelasticity of ethylene-co-methacrylic acid copolymer (EMAA) and its ionomers (EMAA-Zn and EMAA-Na) has been measured in the melt state. The time-temperature superposition principle is applicable to data of angular frequency dependences of storage modulus (G') and loss modulus (G") for EMAA very well from 140°C to 200°C. On the other hand, data for ionomers give two separated master curves with different temperature dependences of shift factor, one from the data obtained in the range of 140°C-170°C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The strength provided to an interface by an adhesive layer is typically increased with an increased coverage of the adhesive over the surfaces being joined. A difference between the thermal expansion coefficient of EMAA and the epoxy resin (approximated as 7-11 Â 10 À4 K À1 [28,29] and 0.6-1.6 Â 10 À4 K À1 [30], respectively) may result in a ''differential expansive bleeding" as suggested previously [16]. In addition to any contributions from ''differential expansive bleeding", the formation of an adhesive layer is promoted by a pressure difference generated during the expansion of small bubbles present in the EMAA particles.…”
Section: Healing Mechanism Determinationmentioning
confidence: 99%
“…The strength provided to an interface by an adhesive layer is typically increased with an increased coverage of the adhesive over the surfaces being joined. A difference between the thermal expansion coefficient of EMAA and the epoxy resin (approximated as 7-11 Â 10 À4 K À1 [28,29] and 0.6-1.6 Â 10 À4 K À1 [30], respectively) may result in a ''differential expansive bleeding" as suggested previously [16]. In addition to any contributions from ''differential expansive bleeding", the formation of an adhesive layer is promoted by a pressure difference generated during the expansion of small bubbles present in the EMAA particles.…”
Section: Healing Mechanism Determinationmentioning
confidence: 99%
“…In a previous paper, 6) we found that the time-temperature superposition principle could be applied to EMAA ionomers in two separate temperature ranges (140°C-170°C and 180°C-200°C), indicating that structural changes of ion aggregates occur between 170°C and 180°C. In order to inspect the effect of ion aggregates on the stress relaxation behavior for EMAA ionomers in the different temperature ranges, we also made the stress relaxation measurement for EMAA ionomers at 200°C.…”
mentioning
confidence: 86%
“…6) This means that structural changes of ion aggregates occur between 170°C and 180°C. In this paper, we studied the stress relaxation behavior of EMAA ionomers under large step shear strains at 140°C and 200°C, and discussed structural changes under large step shear strains.…”
mentioning
confidence: 99%
“…The participation of these copolymers would possibly initiate the formation of ionomers with CaCO 3 . The dynamic viscoelasticity of copolymers, such as EMAA, and its ionomers (usually EMAA-Zn and EMAA-Na) had been studied in the melt state by Zeng, 10 where, even at 200°C , the storage modulus G# and loss modulus G$ are much higher than those of pristine copolymer EMAA. The structural change in EMAA ionomers occurs between 170°C and 180°C.…”
Section: Rheological Behaviormentioning
confidence: 99%